Clinical features of aseptic meningitis with varicella zoster virus infection diagnosed by next-generation sequencing: case reports - Chen, Lanlan (BMC Infect Dis, 2020)
BACKGROUND: The aseptic meningitis caused by varicella zoster virus (VZV) reactivation was less described in the literature, most of which were detected by means of polymerase chain reaction. The authors presented 4 adult immunocompetent patients with acute aseptic meningitis with VZV infection diagnosed by next-generation sequencing (NGS). CASE PRESENTATION: Four patients were admitted to the hospital with headache and fever between March 2018 and August 2019. The median ages were 37 years (range 22–52 years). The median symptoms onset to clinic time was 3.5 days (range 3–6 days). Two patients had signs of meningeal irritation. Rash occurred after the meningitis symptoms in 1 patient (time from meningitis symptoms to rash, 2 days). No other sign or symptom was reported. The brain Magnetic resonance imaging and electroencephalography were normal in all patients. Cerebrospinal fluid (CSF) samples were obtained at a median of 4 days (range 3–7 days) from the meningitis symptoms onset. Opening pressure of lumbar puncture after admission were high in these cases (median 256 mm H(2)O; range 165–400 mm H(2)O). White blood cell counts and protein levels were significantly elevated in CSF samples (median 317 × 10^6/L, range 147–478 × 10^6/L; median 1.41 g/L, range 0.57–1.79 g/L). The cytology of CSF demonstrated a lymphocytic pleocytosis, and most multinuclear cells. The culture of CSF was negative for all 4 cases, while T-cell spot test was positive for 2 cases, who were administrated with anti-tuberculosis treatment for suspicious tuberculous meningitis. NGS of CSF (the Vision Medical Research Institute) detected specific sequences of VZV in the 4 cases within 72 h after admission. The inappropriate treatment were stopped while acyclovir were continued intravenously for 10–14 days. All patients recovered completely. CONCLUSIONS: VZV is an infectious agent that causes aseptic meningitis in immunocompetent adults and could not be accompanied by skin manifestations. The NGS of CSF is a rapid detection for the identification and differentiation of meningitis in patients, which is of great importance for providing the rapid and accurate diagnosis and the targeted antimicrobial therapy for central nervous system infection.